Magnitude of exposure and perception of second hand smoking among rural population in Trichy, Tamil Nadu - K., Hemalatha; R., Varunkumar; S. J., Vandana (International Journal Of Community Medicine And Public Health, 2017)
Background: India is one of the countries where tobacco use is highly prevalent. Tobacco use in the form of smoking is related to occurrence of multiple health related problems in smokers and also general population. Methods: A community based cross sectional study was conducted among 360 adults residing in a rural area of Tiruchirappalli. Cluster sampling was used to select the study participants. A pretested semi-structured questionnaire was used to obtain information on tobacco use, exposure to environmental tobacco smoke (ETS), knowledge on its health effects and protection measures. Data was entered and analyzed using Epi info 7.2. The results were presented in the form of mean and percentage. Chi-square was used to find the association between the parameters and ETS. A p value of less than 0.05 was taken as significant. Results: Mean age of the study group was 38.5±10.8 years. Proportion of males and females was 53.9% and 46.1% respectively. Two hundred and fifty five (70.8%) were non-smokers and 29.2% have ever smoked some form of tobacco product. Thirty seven percent of the non-smokers were exposed to Environmental Tobacco Smoke in the past 15 days and exposure was higher among males (46.7%) than females (31.3%) (χ2 value=6.3; p=0.014). Public place was the most common place of exposure (25.5%) to ETS. Significantly higher proportion of smokers had correct knowledge on ill effects of ETS than smokers (χ2 value=12.3; p= 0.0004). Conclusions: Exposure to environmental tobacco smoke was significantly high in the study population. Either strict enforcement of laws or banning cigarette sale completely would help reducing the exposure to cigarette smoke which is an important risk factor for multiple non communicable diseases.